Enhancing Cooperative Learning in Groups in Mathematics: The Case of Akesta General Secondary and Preparatory School Grade 12 Section “A” Students - Lencha Tamiru; Dejene Lema; Tesfalem Dandre (Research Parks Publishing LLC, 2021)
This study was aimed to enhance students’ active participation toward cooperative learning in groups in Mathematics. A case study with the involvement of Akesta General Secondary and Preparatory School Grade 12 section “A” students were considered. Questionnaires as tools for the collection of data were used. Even though students like cooperative learning, the findings reveal that their participation on the given group work are too low except the group leaders. It was analyzed that teachers need to assign roles to each and every individual group member to enhance students’ commitment on cooperative learning